Clinical Profile and Management of Rheumatic Heart Disease in Children and Young Adults at a Tertiary Cardiac Center in Indonesia - Lilyasari, Oktavia; Prakoso, Radityo; Kurniawati, Yovi; Roebiono, Poppy S.; Rahajoe, Anna Ulfah; Sakidjan, Indriwanto; Harimurti, Ganesja M. (Frontiers in Surgery, 2020)
Introduction Rheumatic heart disease (RHD) remains a major public health issue affecting children and young adults in developing countries. The study aimed to evaluate the clinical characteristics, management, and reactivation of RHD among children and young adults. Method This was a hospital-based retrospective study conducted at National Cardiovascular Center Harapan Kita, Indonesia; we retrieved relevant data from patients diagnosed with rheumatic heart disease between 2012 and 2018. Results 279 patients were diagnosed with rheumatic heart disease, of which 108 were children, the mean age was 12.02  3.36 and 171 were young adults, the mean age was 24.9  3.84. RHD was more common in female than male young adults (1.5:1). Carditis (63.79%) and fever (23.65%) were the two most commonly seen criteria seen in both populations. Congestive heart failure was common in children group (11.11%), while pulmonary hypertension was present in 19.95% young adult cases. Overall, mitral valve (either isolated or combined) was the most affected valve across age groups (92.83%). The combination of mitral stenosis and tricuspid regurgitation was the predominant in young adult (12.86%) while mitral and tricuspid regurgitation in children (29.62%). There was a high rate of rheumatic tricuspid valve disease (69.17%) and occurrence of quadrivalve lesion especially in children (12.96%). Reactivation of RHD (36.11%) was more common in children. Valve repair was more common in children (49.07%) and replacement in young adults (32.16%) with low in-hospital mortality. Compliance to secondary prophylaxis was a significant challenge. Conclusion Chronic rheumatic heart disease often presented with complications of the disease or reactivation of RF. Inadequate treatment of RF/RHD leads to extensive valvular damage and consequent disabilities. Efforts for active early diagnosis and prompt treatment of RF/RHF and effective preventive measures are essential.